Preparation of an optimized ciprofloxacin-loaded chitosan nanomicelle with enhanced antibacterial activity. (3rd August 2018) - Farhangi, Mahdieh; Kobarfard, Farzad; Mahboubi, Arash; Vatanara, Alireza; Mortazavi, Seyed Alireza
Abstract: Objective: The objective of this study was to evaluate the effect of lipid structure on physicochemical properties of chitosan-fatty acid nanomicelles and prepare an optimum ciprofloxacin-loaded formulation from these conjugates which could enhance the antibacterial effects of drug against some important pathogens like P. aeruginosa. Significance: Nowadays, resistance in infectious diseases is a growing worldwide concern. Nanocarriers can increase the therapeutic index and consequently reduce the antibiotic resistance. By site-specific delivery of drug, the adverse effects of broad-spectrum antibiotics such as ciprofloxacin would be reduced. Methods: Fatty acid grafted chitosan conjugates were synthetized in the presence of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide. The effects of fatty acid type (stearic acid, palmitic acid, and linoleic acid) on physicochemical properties of conjugates were investigated. Ciprofloxacin was encapsulated in nanomicelles by thin film hydration method. Also, the preparation process was optimized with a central composite design. The antibacterial effect of optimum formulation against P. aeruginosa, K. pneumoniae, and S. pneumoniae species was determined. Results: All conjugates were synthetized with high yield values and the substitution degrees ranged between 2.13 and 35.46%. Ciprofloxacin was successfully encapsulated in nanomicelles. The optimum formulation showed high drug loading (≈ 19%), with particle size of about 260 nm and a sustained release profile of ciprofloxacin. The minimum inhibitory concentrations of ciprofloxacin in optimum formulation against P. aeruginosa and K. pneumoniae species were 4 and 2 times lower in comparison with the free drug, respectively. Conclusions: The antibacterial effect of ciprofloxacin was improved by encapsulation of drug in chitosan nanomicelles.